Does Education in Oral Health Competencies in Physician Assistant Education Programs Translate to Delivery of Oral Health Services in Clinical Practice?. Issue 2 (June 2021) - Langelier, Margaret; Surdu, Simona
Abstract : Purpose: The purpose of this study was to determine the extent to which physician assistants (PAs) are educated in oral health competencies and the relationship of education to providing oral health services to patients. Methods: The study was conducted in 2016 by administering an Internet-based survey to a nationwide sample of 2014 graduates of programs accredited by the Accreditation Review Commission on Education for the Physician Assistant. The survey response rate was 12.7% (N = 304). Results: More than half of the PAs who received education in oral health in their professional education programs indicated that oral health curricula were either integrated into one or several topical areas in the base curriculum or delivered in stand-alone lectures. The majority of PA respondents rated their educational preparation as good or excellent in helping them provide oral health education to their patients (54.8%), make appropriate referrals to oral health providers (53.7%), and provide preventive oral health services (51.2%), while more than 40% rated their preparation as good or excellent in helping them identify oral diseases, conditions, and intervention strategies. More than one-third (35.7%) of all PA respondents reported that they provided oral health services in their clinical practices. PAs who received instruction in oral health competencies through the PA education curriculum or from other sources were 2.82 times more likely to provide oral health assessment and screening services to their patients (95% confidence interval, 1.19–6.67). The PA respondents' provision of oral health services was also significantly associated with working in primary medicine or urgent care practice specialties but not with the work setting. Conclusions: PAs educated in oral health competencies are more likely to provide such services to patients, especially in primary medicine or urgent care settings.